Immigrants, Institutions & Inequality: Why US Congress Must Enact Progressive Immigration Reform - Abbasi, Ghazah (Migration Letters, 2024)
This paper focuses on two aspects pertaining to immigrants, institutions, and inequality in the US. The first aspect is how the institution of the US presidency constructs social inequalities among immigrants. Through a comparison of the Biden and Trump administrations, I show that Democratic and Republican Presidents alike perpetuate inequalities among immigrants. The institutional construction of inequality within the immigrant population renders a significant proportion of immigrants deportable. Thus, Congress must pass laws to create pathways for the long-term, legal inclusion of immigrants vulnerable to deportation. The second aspect addressed in this paper is whether immigration reform in the US is best pursued by Congress or the President. I review scholarly opinion on this topic. Conservatives argue for greater control for Republican presidents and a lesser role for Democratic presidents. Progressives argue for a greater role for Democratic Presidents. I contribute to this literature by taking an altogether different stance. In contrast to the positions outlined, I argue that progressive immigration reform should come from Congress because it is the legislative body with the capacity to offer long-term solutions to the systemic deportability faced by immigrants.